Ethnobotanical Analysis of Medicinal Plant Utilization by Local Communities - Poneke, Wildy Vendy; Pasambuna, Henratno; Pobela, Elva; Gilalom, Trisno (Fakultas Kehutanan Universitas Mulawarman, 2025)
This study aims to analyze the use of medicinal plants by local communities in the Toraut area of Bogani Nani Wartabone National Park, using an ethnobotanical approach. Data were collected through interviews with respondents and analyzed descriptively and quantitatively using the Informant Consensus Factor (ICF) and Fidelity Level (FL). The analysis results showed a very high consensus (ICF = 1.00) across seven disease categories, such as body odor, sore throat, bone fractures, and kidney disease, dominated by certain species such as Forest Betel (Piper caducibracteum), Sesewanua (Clerodendron sp.), and Forest Starfruit (Averrhoa bilimbi). The highest FL value (100%) was found for specific species-benefit pairs, including Kayu Arang (Cratoxylon celebicum) for diarrhea and vomiting and Mayana (Coleus atropurpureus) for increasing stamina. Most species exhibited low to medium FL values, indicating their multi-indication nature. The species with the highest frequency of mention, namely Sesewanua, Forest Betel, Tiger Grass, Forest Starfruit, and Forest Mangosteen, are key plants that play an important role in traditional medicinal practices. These findings emphasize the importance of conservation efforts, pharmacological validation, and preservation of local knowledge to support the sustainable use of medicinal plants.